Strategi Kemasan Tari Gayam Karya Nefria Lelyana dalam Mendukung Pelestarian Situs Sendang Gayam - Amalia, Lintang Husna; Istiandini, Winda; Wahyuningtyas, Tri (Mahesa Research Center, 2025)
Madiun City has one site in the center of the city which is called the Sendang Gayam Site. This site has a historical story and there is an air source that is considered to have properties, but its existence is still little known by the wider community. Gayam Dance was created as a work of art that seeks to preserve historical stories and values. This research aims to analyze the Gayam Creation Dance by Nefria Lelyana as an effort to preserve the Sendang Gayam Site in Madiun City using descriptive qualitative methods and collecting data sources through observation, interviews, and documentation. The concept of smooth and firm movements in this dance uses an East Javanese style. Floor patterns use vertical, horizontal, and zig-zag patterns. The number of dancers in this dance is five people. The accompaniment composition uses traditional Javanese musical instruments with pelog tunings. The choice of costumes is dominated by blue as a symbol of the Sendang Gayam Site and the dancers' make-up is simple. Dance props include kendhi, white cloth, blue cloth, and white bag. The location of the dance performance is not always on the site but can be performed at various events. Gayam Creation Dance is a medium for introducing the cultural potential of Madiun City and presenting a strong cultural identity. This dance shows how art can be a bridge between tradition, history, and current needs in efforts to preserve culture